Ein kurzer Beitrag zum Massenwechsel der Gemeinen Kiefernbuschhornblattwespe, Diprion pini (L., 1758) in Beytepe bei Ankara (Hymenoptera: Diprionidae). - Kiziroglou, Ilhami; Turan, Levent (Contributions to Entomology = Beiträge zur Entomologie, 2007)
The Common Pine Sawfly, D. pini L., has damaged all pine (Pinus nigra L.) trees in various sections and completely destroyed 14,0% of them. The number of eggs encountered in an egg stack is between 16-25, and the frequency rate of this is 30,4%. Here the role of the needle is important. The summer generation of D. pini population in Beytepe left eggs on 13,7% of the needles. The parasitization rate of Cocoons is 1,1% for male Cocoons and 14,1% for female Cocoons. Unless unopened and parasitized Cocoons are ignored, the female rate reaches 54,1%. When the widths of female and male Cocoons are compared, female Cocoons are significantly wider with a value of p>0,05. The difference between the lengths of female and male Cocoons is not significant.KeywordsPopulation ecology, population dynamic, widths of cocoons, Coccons parasitized.